A study on factors that influence consumer intention of food delivery applications during covid-19 quarantine among University Malaysia Kelantan students - Anis Syamila Iman; Azri Iskandar Fadlun; Chew Jia Yi; Izzatun Husna Mohd Sobri (2023)
The purpose of this study was to find out the factors that influence consumer intention of Food Delivery Application during the Covid-19 quarantine among University Malaysia Kelantan students. This study also evaluates the continuance usage intention the Food Delivery Application as well as determine the factors that influence the intention to use the Food Delivery Application during the Covid-19 quarantine among UMK students. In this research, the continuance usage intention in the Food Delivery Application is determined through effort expectancy, food and beverage quality, performance expectancy and price saving towards the Food Delivery Application. Online surveys were distributed vis Google Forms to respondent and analyzed with using SPSS and SmartPLS software. The findings of the study show that there is a significant relationship between the continuance usage intention and the factors of food and beverage quality, which is presentation, meeting expectations as presented quality and the quality of the meal as in the restaurant on the Food Delivery Application. Therefore, this study recommendations for the the researcher needs to select a larger population to obtain better quality data and more respondents to answer the prepared survey and researcher also need to do more focus on practical and understandable research methods and questions in a larger population group.